The European transition to a green energy production model: Italian feed-in tariffs scheme & Trentino Alto Adige mini wind farms case study; La transicioń europea a un modelo de produccioń de energiá verde: Esquema italiano de tarifas y estudio de caso de mini parques eoĺicos de Trentino Alto - Javier Heredia Yzquierdo; Antonio Sańchez-Bayoń (Small Business International Review (SBIR), 2020)
The Europe 2020 Strategy is aimed at making the EU into a smart, sustainable and inclusive economy by 2020. This Strategy has to promote environmental policies and economic opportunities. Back in 2007 Italy was performing slightly below average and way below the most advanced EU Member States as far as percentage of green energy of the total energy produced in Italy. Measures were taken and though the Italian regulation around green energies has been hectic though effective. Italian legislation recently passed will put emphasis on the relevance of a Green Power strategy by guarantying an attractive minimum price per Kw produced through clean and environmental friendly sources, notably from Wind energy sources. Within the sector a new area is grafting attention: the mini wind farms. The Trentino Alto Adige region in Northern Italy has taken particularly profit of the national legal framework and has develop a further regional frame that has placed the region on top of the Italian green energy production charts. The local idiosyncrasy is making of the mini wind farms a case study. – – La Estrategia Europa 2020 tiene como objetivo convertir a la UE en una economiá inteligente, sostenible e integradora para 2020. Esta estrategia ha de generar polit́icas medioambientales y oportunidades econoḿicas. Hacia 2007, Italia se comportaba ligeramente por debajo del promedio y muy por debajo de los Estados miembros maś avanzados de la UE en la produccioń de energiá verde como porcentaje de la energiá total producida en Italia. Se tomaron medidas y, aunque la regulacioń italiana en torno a las energiás verdes ha sido voluble, sih́a resultado efectiva. La legislacioń italiana recientemente aprobada pone eńfasis en la relevancia de una estrategia de energiá verde al garantizar un precio mińimo atractivo por Kw producido a traveś de fuentes limpias y amigables con el medio ambiente, especialmente de fuentes de energiá eoĺica. Dentro del sector, una nueva aŕea que estaátrayendo atencioń son los mini parques eoĺicos. La regioń de Trentino Alto Adige en el norte de Italia se ha beneficiado particularmente del marco regulatorio nacional y ha desarrollado un nuevo marco local, que ha colocado a la regioń en la cima de las listas italianas de produccioń de energiá verde. La idiosincrasia local estah́aciendo de los mini parques eoĺicos un caso de estudio.
Keywords: F53; G14; K23; O32; 650; energy transition; green energy; Europe 2020; wind energy; mini wind farms; transicioń energet́ica; energiá verde; Europa 2020; energiá eoĺica; mini parques eoĺicos